2005
DOI: 10.1177/0040517505053811
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Vapor Transport Behavior of Polyester Knit Fabrics

Abstract: A test method that measures microclimate drying time is used to compare the ability of different knit materials to dissipate moisture vapor from a saturated clothing environment to the ambient atmosphere. The performance assessment provided by this novel method is compared with those from common test methods. The latter include measures of the moisture vapor transmission rate provided by the upright cup and the evaporative thermal resistance provided by the sweating guarded hot plate procedure. Upright cup and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 7 publications
5
62
0
1
Order By: Relevance
“…1,15 Meanwhile, the water content distributions in the fibers are not significantly related to temperature distributions. 14 Prahsarn et al 2 studied a test method that measures microclimate drying time, which is used to compare the ability of different knit materials to dissipate moisture vapor from a saturated clothing environment to the ambient atmosphere. They used polyester fabrics with different construction, yarn types, and fiber features.…”
Section: And Yoon and Buckleymentioning
confidence: 99%
“…1,15 Meanwhile, the water content distributions in the fibers are not significantly related to temperature distributions. 14 Prahsarn et al 2 studied a test method that measures microclimate drying time, which is used to compare the ability of different knit materials to dissipate moisture vapor from a saturated clothing environment to the ambient atmosphere. They used polyester fabrics with different construction, yarn types, and fiber features.…”
Section: And Yoon and Buckleymentioning
confidence: 99%
“…They attributed these differences to the fact that hydrophilic fibers retained water molecules and could even swell to reduce the porosity of the fabrics. Prahsarn et al [6] reported that water vapor transmission rate was strongly correlated with fabric thickness, and fiber-related factors such as cross-sectional shape and moisture absorbing properties did not play a significant role. Also, in the literature it was shown that water vapor permeability was in close relation to air permeability [28].…”
Section: Water Vapor Permeability Of Fabricsmentioning
confidence: 99%
“…Absorption of sweat and its transportation through and across the fabric are related to clothing comfort properties of the fabrics. [6][7][8][9][10][11] Drying time is another important aspect while determining a comfort level. 12 There is a general agreement that fabric thickness, density and porosity are critical factors to determine comfort perceptions.…”
Section: Introductionmentioning
confidence: 99%